Study on awareness and knowledge regarding Janani Suraksha Yojana (JSY) among ANC registered women in a primary health centre of tribal area of Thane District of Maharashtra - Singh, Vijaykumar S.; Chavan, Smita S.; Giri, Purushottam A.; Suryavanshi, Somnath R. (International Journal of Research in Medical Sciences, 2017)
Background: In an attempt to make primary health care services available, especially, to the poorest and most vulnerable segments of rural & tribal society, JSY forms a crucial component of the NRHM. JSY is a safe motherhood intervention initiated to reduce maternal and neo-natal mortality and increasing institutional deliveries in them. Objective: 1) To assess awareness about Janani Suraksha Yojana (JSY) among ANC registered women. 2) To establish association of socio-demographic factors with awareness about Janani Suraksha Yojana (JSY). Methods: A cross sectional study was conducted in Primary Health Centre, Khardi of Thane district of Maharashtra during the period of Oct. 2010. A total of 110 ANC registered women were interviewed using pre-designed questionnaire. Results were analyzed by using SPSS version-15. Chi-square test was applied and p < 0.05 was considered as statistically significant. Results: More than half of the women (52.7%) were aware about this governmental scheme & only 17.24% of them were able to answer the correct name of the scheme. They obtained this knowledge mainly from the ANMs (58.6%), AWWs (22.4%) and ASHAs (17.2%). About 54.5% women had the knowledge about the components of JSY. Poor socioeconomic class, backward caste (SC/ST) & skilled/unskilled type of occupation were found to be significantly associated with the presence of knowledge about JSY. Conclusion: As the awareness and knowledge in our study group was less compared to other studies, there is a need to intensify the efforts to increase awareness and knowledge about JSY.